Math, asked by anurag233573, 1 year ago

Let f : N → Y : f(x) = 4x2+12x + 15, Y = Range(f) show that f is invertible and find f-1.​

Answers

Answered by Anonymous
2

Answer:

Hello.  I hope this helps you.  Have a good day.

f is invertible

<=> f is one-to-one (injective) and onto (surjective)  (i.e. f is  bijective)

Since Y is defined as the range of f, it is automatically onto (surjective).  This means that for every value y∈Y there is an x such that y=f(x).

So to show that f is invertible, we just need to show that f is one-to-one (injective)...

f(a) = f(b) for a, b ∈ N

=> 4a² + 12a + 15 = 4b² + 12b + 15

=> a² + 3a = b² + 3b

=> a² - b² + 3a - 3b = 0

=> ( a - b ) ( a + b ) + 3 ( a - b ) = 0

=> ( a - b ) ( a + b + 3 ) = 0

=> either a = b  OR  a + b + 3 = 0.

Since a, b ∈ N, it is not possible for a + b + 3 = 0.  Therefore a = b.

We've shown that if f(a) = f(b), then a = b.  That is, we've shown that f is one-to-one.  Therefore f is invertible.

---------------

To get a formula, let y = f^{-1}(x).  We want a formula for y in terms of x.

y = f^{-1}(x)

<=> x = f(y)

<=> x = 4y² + 12y + 15

<=> 4y² + 12y + (15-x) = 0

<=> y = ( -12 ± √( 12² - (4)(4)(15-x) ) ) / (2)(4)

        = ( -3 ± √( 9 - (15-x) ) ) / 2

        = ( -3 ± √( x - 6 ) ) / 2

Since y ∈ N, so y is a positive value, only the "+" sign here is possible, so we conclude that

f^{-1}(x) = ( -3 + √( x - 6 ) ) / 2

Similar questions